Strategy emergence in service delivery networks: Network‐oriented human resource management practices at German airports. (8th June 2020) - Sydow, Jörg; Wirth, Carsten; Helfen, Markus
Abstract: Organisational restructuring towards vertical disintegration and the accompanying rise of service delivery network (SDN) calls for closer attention, studying whether and how work and employment are strategically managed across organisational boundaries. In this paper, we adopt a "strategy‐as‐practice" approach to explain the emergence of an Human Resource Management (HRM) strategy which is geared towards managing work across organisational boundaries. Based on a comparison of two German major hub airports, we find that differences in network‐oriented HRM strategising in areas such as recruiting, remuneration and training result from micro‐political game playing. In this piecemeal process, management as well as external and internal stakeholders such as workers' representatives, and local and federal politicians participate by using their inter‐organisational relationships and institutionalised power resources to shape a network‐oriented HRM practice. With these findings, we contribute not only to HRM research from a strategy‐as‐practice perspective that is sensitive to institutions, but also to research on inter‐organisational collaboration that has neglected issues of HRM so far, by and large.